Redistributive taxation in the modern world - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2016)
Academic discussion of justice and taxation has focused on determining the moral limits of taxation. This article is concerned specifically with the moral limits on the redistributivity of taxation. Rawlsian principles enable us to determine the moral upper and lower bounds of redistribution through tax and transfer systems. However, major changes since Rawls and Nozick prompt a re-examination of these bounds in the modern context. Increased affluence means that for many societies the worst-off citizens are well-off in absolute terms. Increased immigration and emigration means that the classical model of a closed society is now obsolete. I consider the basis for the taxation of citizens, permanent residents and immigrants based on associative and contractarian models of obligation. The increasing prevalence of incorporation and other legal persons requires a development of the traditional model. Building on the taxation of trusts, I propose a hybrid model between personification and transparency for corporations.